Disorganisation of intermediate filament structure in alcoholic and other liver diseases. Issue 7 (July 1986) - Barbatis, C; Morton, J; Woods, J C; Burns, J; Bradley, J; McGee, J O
Abstract : The distribution of Mallory body antigens JMB1 and 2 was examined in 82 human fresh diagnostic needle liver biopsies and 28 necropsies by the indirect immunoperoxidase technique using 2 monoclonal antibodies (anti-JMB1 and 2) against Mallory bodies. The JMB1 antigen was detectable in bile duct epithelium and in hepatocytes of histologically normal livers. It was also found in all Mallory bodies in various hepatic disorders. This antigen was markedly increased in the cytoplasm of all liver cells in acute alcoholic hepatitis superimposed on alcoholic cirrhosis, in most cases of acute alcoholic hepatitis, and in severe fatty infiltration of the liver with or without Mallory body formation. Mallory bodies contained this antigen but the cytoplasm of Mallory body containing cells lacked JMB1. In normal liver the JMB2 antigen was localised on the cytoplasmic intermediate filament network of hepatocytes and bile duct epithelium; and almost all Mallory bodies also contained this antigen but the adjacent cytoplasm of these cells lacked JMB2. In severe alcoholic liver disease these antigens could not be detected in large zones of hepatocytes even when these hepatocytes did not contain Mallory bodies. It is evident that there is disorganisation of intermediate filament constituents in severe alcoholic liver disease.